Haunted homes - Schweitzer, Dahlia (Quick takes., 2021)
"Exploring a crucial yet critically underappreciated trope of horror-the haunted house-Haunted Homes illuminates the ways in which it has come to signify the anxieties, traumas, and terrors of suburban American life. Surprisingly comprehensive and eminently readable, this slim volume establishes beyond a doubt that in movies and television series from The Conjuring to The Haunting of Hill House, "home is where the horror is." Haunted Homes is unique in its focus on what Schweitzer calls the "suburban gothic." Scholarly studies of the supernatural in horror cinema tend to be decidedly ahistorical, suggesting that contemporary films about haunted houses tap into the same fear of the uncanny evoked by eighteenth and nineteenth-century works of European gothic literature. Schweitzer, however, argues that these films are distinctly modern and American, framing them as a dark reflection of suburban life since the 1950s and particularly in the decade following the economic collapse of 2008. Schweitzer undertakes an in-depth examination of the history of suburbia in the United States as well, offering a detailed and informed account of its origins and development. This is a fresh and original approach. It opens up a new way of seeing haunted homes in recent horror cinema and television, setting her book apart from others on the topic. This is consequently a book that will appeal to a wide range of readers, from film scholars and students to fans of the horror genre"--